2020
DOI: 10.1103/physrevresearch.2.013163
|View full text |Cite
|
Sign up to set email alerts
|

Characterizing the many-body localization transition by the dynamics of diagonal entropy

Abstract: Based on the dynamics of diagonal entropy (DE), we provide a nonequilibrium method to study the properties of many-body localization (MBL) transition including the critical point and the universality class. By systematically studying the dynamical behaviors of DE in the fully explored Heisenberg spin chain with quasiperiodic field, we demonstrate the DE method can efficiently detect the transition point W c between the thermal and MBL phase. We further use the method to study the MBL transition in the isotropi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

1
9
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
5
4

Relationship

0
9

Authors

Journals

citations
Cited by 17 publications
(10 citation statements)
references
References 68 publications
1
9
0
Order By: Relevance
“…Polkovnikov showed that it had all the good properties that we can expect from a suitable definition of entropy. This diagonal entropy has already been investigated by many authors [9][10][11][12][13]. We can directly show that the diagonal entropy of the pure state (4) is the von Neumann entropy of the density matrix (16) obtained from a decoherent process.…”
Section: A Statistical Point Of Viewmentioning
confidence: 71%
“…Polkovnikov showed that it had all the good properties that we can expect from a suitable definition of entropy. This diagonal entropy has already been investigated by many authors [9][10][11][12][13]. We can directly show that the diagonal entropy of the pure state (4) is the von Neumann entropy of the density matrix (16) obtained from a decoherent process.…”
Section: A Statistical Point Of Viewmentioning
confidence: 71%
“…The diagonal entropy exhibits most of the properties of a thermodynamic entropy, including additivity, conserved in the adiabatic process and increases when an equilibrium system is taken out of equilibrium. Hence, it is an appropriate entropy for the studies of the nonequilibrium dynamics in an isolated quantum systems and has been employed in diverse areas of physics [46][47][48][49][50]. Moreover, S d is consistent with the well-known von Neumann's entropy for systems in equilibrium.…”
Section: Introductionmentioning
confidence: 73%
“…Moreover, S d is consistent with the well-known von Neumann's entropy for systems in equilibrium. It is also worth mentioning that since the diagonal entropy only involves the diagonal part of the density matrix, it can be experimentally measured in an efficient way [50].…”
Section: Introductionmentioning
confidence: 99%
“…Even though the former discussed the role of interactions in the localization physics described therein, the latter sparked great interest in the topic, considering dynamical aspects including the whole spectrum not limited just to the ground state localization ques-tion. Since then, many works, both theoretical and experimental, have addressed the topic of many-body localization 14,[18][19][20][21][22][23][24][25][26][27][28][29][30][31][32][33][34][35][36] . Many-body localization is the survival of some remnant of Anderson localization in the presence of interactions.…”
Section: Introductionmentioning
confidence: 99%